2012
DOI: 10.1590/s1516-14392012005000147
|View full text |Cite
|
Sign up to set email alerts
|

Surface cellulose modification with 2-aminomethylpyridine for copper, cobalt, nickel and zinc removal from aqueous solution

Abstract: Cellulose was first modified with thionyl chloride, followed by reaction with 2-aminomethylpyridine to yield 6-(2'-aminomethylpyridine)-6-deoxycellulose. The resulting chemically-immobilized surface was characterized by elemental analysis, FTIR, 13 C NMR and thermogravimetry. From 0.28% of nitrogen incorporated in the polysaccharide backbone, the amount of 0.10 ± 0.01 mmol of the proposed molecule was anchored per gram of the chemically modified cellulose. The available basic nitrogen centers attached to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 54 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…The incorporation of this alkaline center, in the cellulose structure, can occur through a variety of chemical reactions, using various nitrogen precursors, such as aminoethanethiol [ 8 ], ethylenediamine [ 10 ], 2-aminomethylpyridine [ 11 ] and 1,4-diaminobutane [ 12 ]. Studies showed, in aqueous medium, an interaction between the nitrogen incorporated to cellulose and contaminants (metals and dyes), in a heterogeneous system using the solid/liquid interface [ 13 ]. For example, cellulose modified by ethylenediamine proved efficient in the adsorption of divalent cations (Cu 2+ , Ni 2+ and Zn 2+ ) [ 14 ], as the cellulose modified by ethylenediamine, with an oxidized cellulose derivative as intermediate, was efficient in the removal of acid red GP, congo red 4BS and reactive light-yellow K-4G anionic dyes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of this alkaline center, in the cellulose structure, can occur through a variety of chemical reactions, using various nitrogen precursors, such as aminoethanethiol [ 8 ], ethylenediamine [ 10 ], 2-aminomethylpyridine [ 11 ] and 1,4-diaminobutane [ 12 ]. Studies showed, in aqueous medium, an interaction between the nitrogen incorporated to cellulose and contaminants (metals and dyes), in a heterogeneous system using the solid/liquid interface [ 13 ]. For example, cellulose modified by ethylenediamine proved efficient in the adsorption of divalent cations (Cu 2+ , Ni 2+ and Zn 2+ ) [ 14 ], as the cellulose modified by ethylenediamine, with an oxidized cellulose derivative as intermediate, was efficient in the removal of acid red GP, congo red 4BS and reactive light-yellow K-4G anionic dyes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is the accumulation of one or more parts in an interfacial layer, and it may occur by chemisorption or physisorption 14,15 . Various materials are used as adsorbents, e.g., chitosan 16,17 , chitin 18 , soybean oil 19 , material based on cyclodextrin 20 , agricultural wastes 21,22 , cellulose 23,24 , and clay minerals 25,26,27 , among others. Among these materials, clay minerals are very interesting solids because they are natural, abundant, easily extractable, usually nontoxic, and relatively inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the nitrogen incorporation in cellulose or in the cellulosic materials is an important chemical modification which allows the insertion of active sites in this biomaterial. These sites can interact in aqueous medium with contaminants molecules, in heterogeneous system in which the interactive processes are defined by solid/liquid interface [25].…”
Section: Aminationmentioning
confidence: 99%
“…The first stage of reaction consists in allogeneic derivative synthesis. In the halogenation, chlorine addition is preferable, since it is the most effective allogeneic, whose preferential sequence is: chlorine > bromine, iodine > fluorine [25]. The first step of reaction series consists in the cellulose chlorination, a favored process by nucleophilic attack from thionyl chloride on hydroxyl group in the biopolymer backbone, resulting in chlorine atom pending in polymer structure.…”
Section: Aminationmentioning
confidence: 99%
See 1 more Smart Citation